Predictable factors for intervention with heparin free plasmapheresis in impending liver cell failure due to consumption of phosphorus rodenticide - Banjan, Deepa S.; Sane, Kavita; Wattamvar, Sachchidanand; More, Mahesh (International Journal of Research in Medical Sciences, 2019)
Background: Yellow phosphorus containing rodenticide poisoning are common in Adult critical care. They cause coagulopathy and liver cell failure in humans. Till date, only liver transplants had been advocated as the final treatment of fulminant liver failure occurring as a complication of rodenticide poisoning. In this study, an innovative Treatment approach was given to liver cell failure cases who had consumed yellow phosphorus paste. Methods: Retrospective analysis of case records of liver cell failure cases due to the consumption of phosphorus containing Rodenticide poisonings, were analysed for a period of 1 year from January 2018 to January 2019 in a public hospital. Medical case records were obtained from records department and Postmortem registers. Symptoms, signs, investigations, treatments, complications, and outcomes were tabulated. Results: Total 11 cases were studied. 8 cases of liver cell failure and coagulopathy in whom therapeutic heparin free plasmapheresis was given, recovered completely from liver cell failure. A significant drop in Haemoglobin, platelet count, PT INR Ratio and rise in serum alkaline phosphatase, were the predictable factors used for the intervention of therapy with 5 cycles of heparin free plasmapheresis to eliminate toxic effects of phosphorus on liver cells and in the blood. A comparative analysis of untreated cases (n=3) vs treated with plasmapheresis (n=8), showed a significant statistical difference (P <0.005) in outcomes with a degree of freedom=2. Conclusions: Plasmapheresis can be a therapeutic treatment for liver cell failure caused due to the consumption of yellow phosphorus. Predictable factors for impending liver cell failure in whom plasmapheresis will be of benefit are dependent upon prothrombin time, INR ratio, Liver enzymes and time interval between consumption and onset of liver cell failure.